2020
DOI: 10.1245/s10434-020-08389-7
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Lymphatic, Venous and Perineural Invasion After Neoadjuvant Chemotherapy in Patients with Gastric Adenocarcinoma

Abstract: Background. The significance of perineural (PNI), lymphatic (LI) and venous invasion (VI) in gastric cancer patients who have received neoadjuvant chemotherapy is unclear. The aim of this study is to determine the incidence and prognostic significance of LI, VI and PNI in these patients. Patients and Methods. Consecutive patients treated with neoadjuvant chemotherapy followed by gastrectomy with D2 lymphadenectomy were reviewed. Presence of LI, VI and PNI was recorded and correlated with clinical outcomes. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 24 publications
3
12
1
1
Order By: Relevance
“…A few authors have evaluated the prognostic significance of LVI and/or PNI after preoperative chemotherapy. Most recently, Woodham and colleagues found that LVI, venous invasion (VI), and PNI were each associated with more advanced ypT and ypN categories, as well as a higher number of positive LNs, after preoperative chemotherapy 11 . These findings are consistent with our findings.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…A few authors have evaluated the prognostic significance of LVI and/or PNI after preoperative chemotherapy. Most recently, Woodham and colleagues found that LVI, venous invasion (VI), and PNI were each associated with more advanced ypT and ypN categories, as well as a higher number of positive LNs, after preoperative chemotherapy 11 . These findings are consistent with our findings.…”
Section: Discussionsupporting
confidence: 92%
“…Many authors have demonstrated a significant association between the presence of LVI and the presence of PNI, findings that were replicated in our study 6,8‐11 . This is important, as our findings demonstrate a significant prognostic impact of concurrent LVI and PNI on OS and DFS, while either factor alone was not independently predictive of survival outcomes.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…This study reveals additional prognostic factors for patients with gastric adenocarcinoma who were treated with neo-adjuvant chemotherapy and surgery. 5 The presence of lymphatic, venous and perineural invasion are features of aggressive tumours. These histological findings in the resection sample may play a prognostic role.…”
Section: Presentmentioning
confidence: 99%